Factors Affecting Internship Students’ Speaking Anxiety - Asnawi Muslem; Ika Apriani Fata; Inayatullah Inayatullah (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
This study is sought to discover the English speaking anxiety factors in class of internship students and to investigate the students’ efforts to cope the problems. This research applied qualitative method in addition research subjects were 30 English internship students of Universitas Syiah Kuala in 2015. The data were collected through questionnaire and interview. Both of the instruments were adapted from (Tum Kunt, 2013). The study discovered that the major factors of students’ speaking anxiety divided into two interrelated groups; psychological and educational factors. Regarding to the psychological factors, the students were anxious and feeling fear of having misunderstanding teachers’ instruction and supervision. The educational factors were reflecting to the current bad performance of speaking skill aspects namely; inaccurate of fluency, inappropriate of vocabulary, inappropriate application of grammar rule, insufficient materials preparation and poor of pronunciation. Nevertheless, 16 internship students who were indicated high level of speaking anxiety used various efforts to solve the speaking anxiety such as; practicing, listening to native speaker’s utterance, reading English texts, memorizing words, keeping using English in class, learning grammar rule, making note, preparing the material and using audio dictionary. This study concludes that everyone has anxiety and it is common, yet this problem could be reduced by doing some efforts